2018
DOI: 10.1186/s40959-018-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler Imaging for anthracycline cardiotoxicity monitoring in pediatric patients with cancer

Abstract: Background: Cardiotoxic effects of anthracycline therapy are a major cause of morbidity for childhood cancer survivors. The aim of this retrospective evaluation is to assess the efficacy of Tissue Doppler Imaging in the early detection of myocardial alterations in these patients. Methods: A population of 50 childhood cancer survivors (32 males and 18 females) who have been treated with anthracyclines was evaluated by standard and TDI echocardiographic examination of the basal and median region of the intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
4
7
1
Order By: Relevance
“…In our group, IVRT and A wave did not change during AC treatment, in opposition to other studies [53][54][55]. E and E/A ratio decreased during therapy (p<0.001, p=0.014), suggesting a dysfunction in LV filling, similar results being encountered in different papers [54][55]. One year after diagnosis, E and E/A ratio returned to baseline values.…”
Section: Discussioncontrasting
confidence: 90%
“…In our group, IVRT and A wave did not change during AC treatment, in opposition to other studies [53][54][55]. E and E/A ratio decreased during therapy (p<0.001, p=0.014), suggesting a dysfunction in LV filling, similar results being encountered in different papers [54][55]. One year after diagnosis, E and E/A ratio returned to baseline values.…”
Section: Discussioncontrasting
confidence: 90%
“…This was in agreement with earlier studies, which found that tissue Doppler parameters, such as LV S, were sensitive to detect early doxorubicin-induced cardiotoxicity. [38][39][40][41] Interestingly, LV FS failed to show any significant decrease after doxorubicin treatment that was in line with the results of other investigators who reported that LV FS and LV ejection fraction (LV EF) were insensitive to detect early doxorubicin-induced cardiotoxicity. 38,39,42,43 Our study revealed that patients with omega 3 treatment showed nonsignificant changes in LV S and 2D-GLS, which suggested that omega 3 fatty acids protect against left ventricular dysfunction induced by doxorubicin.…”
Section: Discussionsupporting
confidence: 90%
“… 24 Moreover, according to another study, the findings consistent with subclinical myocardial diastolic impairment could be detected by TDI, even in patients with only a follow-up period of 2 years after the completion of chemotherapy. 25 It is known that diastolic dysfunction caused by cardiomyocyte damage related with systemic disorders may often progress to heart failure, in which systolic functions are preserved. 26 , 27 In the present study, the detection of longer duration of the TDI-derived IVRT in CCSs was consistent with the subclinical impairment in left ventricular diastolic functions.…”
Section: Discussionmentioning
confidence: 99%